A literatura infantil no Espírito Santo no séc. XXI e o desvelar do autor-distribuidor - Oliveira, Ivana Esteves Passos de (2015)
The children's literature chain in Espírito Santo – which beginnings are found in the 1980 decade, towards the 1990 decade, mainly with the emergence of the cultural incentives laws – comes growing to the XXI century, but with at least two impediments to its setting: the divulgation and the circulation of the children’s books produced in Espírito Santo. Contemporary, the independent publishing is the most frequent praxis: an author who produces, publishes, advertises and distributes his books, without an organized editorial-literary support. To understand the handicrafty dynamics of this children’s literature in Espírito Santo, a ethnographic research methodology was sought, with the consubstantiation of the genetic critical studies, ant it aims to know discourses and practices related to five writes that are involved with children’s literature chain in Espírito Santo (Elizabeth Martins, Francisco Aurélio Ribeiro, Ilvan Filho, Neuza Jorden and Silvana Pinheiro), that could let us see, by transcribed interviews and primary documents, traces of the children’s book production chain. Procedures and processes are studied where the author is impelled to transmute himself in roles other than the aesthetic creation. The children’s books writers in Espírito Santo articulations and the modus operandi were sought as mechanism to unveil the children's literature chain in the targeted context. The goal of this study is to outline a radiograph of the field, that articulates the local context to the other contexts. Among the theorists who we were based on, Hunt, Lajolo, Zilberman and Coelho (children’s literature in the world and in Brazil), Fonseca Reis (production chain in culture), Willemart (genetic critical studies) and diferent autors that writes about ethnographic research are highlighted.